DESIGN AND IMPLEMENTATION OF PIEZOELECTRIC TRANSDUCER TO IMPROVE FISHING EFFICIENCY ON BAGAN BOAT - Muhammad Ilham; Manik, Henry M.; Rahmat, Ayi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
The decline in fish catches among bagan boats in Labuhan Jambu, Sumbawa District, is caused by overfishing, illegal fishing, and climate change. To address this issue, technological innovations such as sonar systems that emit acoustic signals to attract fish are necessary. This study aims to design piezoelectric transducers and transmitter drivers capable of emitting acoustic frequencies that effectively attract fish around bagan boats, thereby increasing catch yields. The methodology included system design, fabrication, and testing. The developed transducer operates across a frequency range of 1–75 kHz, and field tests were carried out by installing the transducer beneath the bagan boat. Results indicated that fish responded quickly to frequencies between 500–800 Hz, as evidenced by the appearance of bubbles on the water surface, suggesting fish presence. The main species caught included pelagic fish, skipjack, and squid. Fish catches increased by approximately 2–3 times compared to conventional methods. The transducer and transmitter driver using piezoelectric materials were successfully developed and functioned effectively. The final prototype was capable of emitting acoustic frequencies from 1 Hz to 100 kHz. This innovation demonstrates the potential of piezoelectric transducer technology to significantly enhance fish catches in bagan boat operations in Labuhan Jambu. Keywords: Driver transmitter, bagan boat, piezoelectric, transducer